Children and young people’s experiences of receiving group metacognitive therapy: Thematic analysis of a transdiagnostic treatment for common mental health problems - Wells, Adrian; Nasseri, Noor; Carter, Karin; Capobianco, Lora (Frontiers in Psychiatry, 2025)
BackgroundMental health problems in children and young people (CYP) are increasing with a pressing need for more effective treatments. However, the development of psychological interventions seldom explores young patients experiences of treatment, which is crucial in understanding factors influencing the uptake, impact and validity of therapy. We aimed to explore for the first time CYP experiences of how they received group metacognitive therapy for anxiety disorders and depression.MethodsA qualitative study was embedded in a larger feasibility RCT (n=95) comparing group-based MCT with treatment as usual. Seventeen CYP aged 11-17yrs who had been part of the group-MCT arm consented to participate. Interviews were semi-structured, open-ended and followed an a-priori guide. Coding and analysis adhered to guidelines for reflexive thematic analysis.ResultsThree overarching themes emerged in patient experiences: treatment fidelity, treatment delivery, and experiences of homework. Treatment fidelity had two subthemes: i) treatment receipt- which included patients understanding of MCT and performance of MCT techniques during the intervention, and ii) treatment enactment- which included performance of MCT techniques in applied settings, plus perceived benefits of treatment. Treatment delivery included two subthemes; i) format of therapy and, ii) therapist characteristics.ConclusionsThe results support the use of MCT in children and young people with mixed anxiety disorders and depression. Patients reported understanding the treatment rationale and benefiting from the intervention. They described, consistent with purported mechanisms, how treatment helped them make a shift in beliefs about thoughts and see worry as powerless and under personal control. Patients described an ability to apply specific techniques in real-life settings, despite noting major challenges with homework compliance. The results emphasised areas that might be improved and important recommendations are made for MCT delivery and practise in children and adolescents.